The Impact of ESG Performance on Firm Financial Risk: Evidence from ASEAN-4 Energy Companies - Muhammad Ayoub (P3M Politeknik Negeri Banjarmasin, 2025)
This article examines the relationship between Environmental, Social, and Governance (ESG) performance and firm-specific financial risk in the ASEAN-4 energy sector, which comprises Indonesia, Malaysia, Singapore, and Thailand. Using a panel data set of 40 listed energy companies from 2020–2024, the article uses fixed and random effects regression models to derive the determinants of firm-level volatility measured by 360-day and 200-day rolling stock returns. The results show that firm size and sales growth explain long-term volatility to a great extent, while inflation is the primary source of short-term volatility. The results suggest that firm-specific factors influence risk over longer time horizons, but macroeconomic volatility dominates in the short term. The findings give evidence to support stakeholder theory and risk management theory by suggesting how ESG-oriented firms can better combat volatility through the use of sustainable strategies and growth policies. Practically, the research informs policymakers of the importance of green financing, stable inflation, and frequent ESG disclosure in promoting sustainable capital markets. The originality of the research is the focus on a less explored region and sector—ASEAN-4 energy companies—offering new empirical proof of the ESG–risk nexus within emerging market settings faced with energy transition challenges.